2013
DOI: 10.1155/2013/943789
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Sensitivity of Thyroid Associated Ophthalmopathy Patients without Obvious Optic Neuropathy

Abstract: Purpose. To compare the contrast sensitivity levels of thyroid associated ophthalmopathy (TAO) patients without obvious optic neuropathy with those of healthy people. Methods. Forty eyes of 20 TAO patients without dysthyroid optic neuropathy and 40 eyes of 20 healthy subjects were evaluated in this prospective case-controlled study. The contrast sensitivity functions (CSFs) of all subjects were measured by the functional acuity contrast test (FACT) in five frequencies which were 1,5 cpd (A), 3 cpd (B), 6 cpd (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In this context, along with optical coherence tomography (OCT), which allows assessment of the morphological features of the optic nerve to some extent, a contrast sensitivity (CS) test can be beneficial in the assessment of the functional feature of the optic nerve, because it may enable determination of visual disturbances, even in the early stages of optic nerve diseases (4,5) . In some (6) . Therefore, patients who may be at risk of optic neuropathy, such as those with pSS, should also be examined using a CS test, although they may have completely normal visual acuity levels according to the Snellen chart.…”
Section: Resultados: O Teste Cs Em Pacientes Pss Não Diferiu Do Que Omentioning
confidence: 99%
“…In this context, along with optical coherence tomography (OCT), which allows assessment of the morphological features of the optic nerve to some extent, a contrast sensitivity (CS) test can be beneficial in the assessment of the functional feature of the optic nerve, because it may enable determination of visual disturbances, even in the early stages of optic nerve diseases (4,5) . In some (6) . Therefore, patients who may be at risk of optic neuropathy, such as those with pSS, should also be examined using a CS test, although they may have completely normal visual acuity levels according to the Snellen chart.…”
Section: Resultados: O Teste Cs Em Pacientes Pss Não Diferiu Do Que Omentioning
confidence: 99%
“…Color vision changes represent an early sign of optic nerve compression. Contrast sensitivity may diminish in TED patients who do not show other signs of DON, indicating this test may detect subclinical optic nerve damage early in the disease process[39]. …”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…It was shown that optic disc function may be affected in TAO patients without obvious optic neuropathy and extraocular muscle swelling [ 4 6 ]. So some diagnostic and follow-up tests were previously used to evaluate the visual function of the patients with TAO, such as visual field test, contrast sensitivity test, visual evoked potential, and color sensation test.…”
Section: Introductionmentioning
confidence: 99%